Circadian Rhythm of Substrate Oxidation and Hormonal Regulators of Energy Balance. (28th May 2020) - Rynders, Corey A.; Morton, Sarah J.; Bessesen, Daniel H.; Wright, Kenneth P.; Broussard, Josiane L.
Abstract : Objective: The circadian system provides an organism with the ability to anticipate daily food availability and appropriately coordinate metabolic responses. Few studies have simultaneously assessed factors involved in both the anticipation of energy availability (i.e., hormones involved in appetite regulation) and subsequent metabolic responses (such as energy expenditure and substrate oxidation) under conditions designed to reveal circadian rhythmicity. Methods: Eight healthy adults (four females; age: 28.0 ± 2.3 years; BMI: 24.3 ± 2.9 kg/m 2 ) participated in a 26‐hour constant routine protocol involving continuous wakefulness with constant posture, temperature, dim light, and hourly isocaloric snacks. Indirect calorimetry was performed every 3 hours for measurement of energy expenditure and substrate oxidation. Subjective hunger was obtained hourly using questionnaires. Saliva and plasma were obtained hourly to assess melatonin (circadian phase marker) and hormones (leptin, ghrelin, and peptide YY). Results: Fat and carbohydrate oxidation was highest in the biological evening and morning, respectively. Subjective hunger ratings peaked during the middle of the biological day. Significant circadian rhythms were identified for ghrelin and peptide YY with peaks in the biological evening and morning, respectively. Conclusions: These findings support a role for the circadian system in the modulation of nutrient oxidation, subjective measures of appetite, and appetitive hormones.